2015
DOI: 10.1080/01419870.2014.992922
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic identity and psychological adjustment in transracial adoptees: a review of the literature

Abstract: International adoption is a relatively recent phenomenon and research in this field is emerging, particularly on issues of ethnic identity development and its implications for psychological adjustment and well-being. This article presents a critical review of the literature on ethnic identity in transracial adoptees as it relates to discrimination and psychological well-being. The review results show no clear evidence on the relation between a strong ethnic identity of origin, racial socialization efforts by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
(89 reference statements)
0
16
0
1
Order By: Relevance
“…Future studies should more thoroughly explore the role of openness in communication regarding adoption, especially with fathers, and test whether the association between parent‐child openness and adoptees' well‐being may be mediated by differential identity processes. For example, based on a number of studies suggesting the crucial role played by ethnic identity in promoting adoptees' psychosocial development (Boivin & Hassan, 2015; Ferrari et al, 2015b) and the intertwinement between adoptive and ethnic identity (e.g., Beaupre et al, 2015; Grotevant, 1997), a further but related avenue for future research may be to consider both adoptive and ethnic identity dimensions as mediators in the association between adoption communication openness and adoptees' psychological well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should more thoroughly explore the role of openness in communication regarding adoption, especially with fathers, and test whether the association between parent‐child openness and adoptees' well‐being may be mediated by differential identity processes. For example, based on a number of studies suggesting the crucial role played by ethnic identity in promoting adoptees' psychosocial development (Boivin & Hassan, 2015; Ferrari et al, 2015b) and the intertwinement between adoptive and ethnic identity (e.g., Beaupre et al, 2015; Grotevant, 1997), a further but related avenue for future research may be to consider both adoptive and ethnic identity dimensions as mediators in the association between adoption communication openness and adoptees' psychological well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…Given the mixed findings regarding the associations between racial socialization, identity development, and psychological adjustment in TRA children, Boivin and Hassan (2015) noted that qualitative designs "can help explore the complexity and the context-bound dynamic links" between these constructs. More research is needed to assess the perceived effects of racial socialization messages for Asian TRA children in particular, as the majority of studies and theories of racial socialization in same-race and adoptive families have historically centered on Black and African American children (Priest et al, 2014).…”
Section: The Present Studymentioning
confidence: 99%
“…Although the self-esteem of adoptees is comparable with that of the general population (Juffer and van IJzendoorn, 2007), identity issues have been described by several researchers (Caballero, et al., 2012; Hübinette and Andersson, 2012; Lind, 2012; Rushton, et al., 2012). Several studies report a significant association between racial, cultural and ethnic socialisation and strong ethnic identity with higher self-esteem and well-being (Basow, et al., 2008; Mohanty, 2013) although others are less conclusive (Boivin and Hassan, 2015; Castle, Knight and Watters, 2011). For example, Tieman and colleagues (2008) showed that young adult adoptees searching for roots had more psychiatric problems.…”
Section: Introductionmentioning
confidence: 99%